(untitled) (Journal of Applied Learning and Teaching, 2020)
This study was conducted to develop and validate a brief instrument to measure the epistemic beliefs of Singaporean polytechnic students. The Brief Epistemic Beliefs Instrument (BEBI) comprised 12 items, organized in four subscales: Malleable Ability (MA), Need for Effort (NE), Fallible Authority (FA) and Evolving Knowledge (EK). The instrument was completed by both groups of students within the research. An Exploratory Factor Analysis (EFA) was used to explore the latent structure of the BEBI on data from polytechnic A, while a Confirmatory Factor Analysis (CFA) was used on data from polytechnic B. While the EFA indicated a three-factor structure for the instrument (in which the factor Fallible Authority – FA – failed to emerge), the CFA confirmed the original four-factor model proposed. Cronbach alphas also indicated moderately high levels of internal consistency for the four subscales. These results suggested the internal structure of the instrument to be sound for use within the Singapore population cohort, although the factor structure of the instrument did appear to differ somewhat across samples.